(untitled) (International Journal of Engineering and Computer Science, 2020)
This research paper focuses on creating a platform for street vendors which will improve their availability to users by displaying their real-time location nearby user’s locality along with their respective services. This doesn’t require any expensive hardware allowing users to get notified when a hawker providing services of user’s interest pass through her street. Small-scaled business people like hawkers have a large impact on a country’s economy because of their large population in developing countries like India. Due to minimal exposure to technology, they use classic business methods which struggle to uphold their position against tough competition from large organizations. These hawkers can be uplifted by providing a platform which will be based on advanced business strategies developed on the basis of those which are introduced by modern economists and business ideologists. This platform will be as useful for static vendors as it is for dynamic vendors not limiting to a single service but to all street vendors present despite the service they provide. Hence, users won’t have to look for vendors floating in the streets as their location will be visible on the map in the application.